Senior High School Mathematics Subjects in Queensland: Options and Trends of Student Participation - Musarurwa David Chinofunga; Philemon Chigeza; Subhashni Taylor (PRISM)
In the State of Queensland in Australia, Years 11 and 12 students can opt to study calculus based or non-calculus based mathematics. Calculus based mathematics subjects are a prerequisite for Science, Technology, Engineering and Mathematics (STEM), which has been identified as critically important for current and future productivity by the Australian government. The objective of this study was to identify broad trends in senior Queensland students’ participation in calculus and non-calculus based Mathematics purely from a statistical viewpoint using a large data set from the Queensland Curriculum and Assessment Authority (QCAA). To this end, trends in Years 11 and 12 students’ participation in calculus based Mathematics B and C, and non-calculus based Mathematics A and Prevocational Mathematics between 2010 and 2019 was investigated. The QCAA data was analysed using quantitative methods to identify trends in student participation in the various mathematics subject options.  The data included number of schools, location, gender, indigenous or non-indigenous, residence status and number of students in different options. The results indicated that more male students opted for Mathematics B and C compared to females, and not all schools offered all options.